(untitled) (Conference on English Language Teaching, 2023)
Morphology is the study of word structure. It means that a word consists of elements or commonly known as morphemes. Animal Farm is a novel by George Orwell. The words contained in this novel can be analyzed to learn morphemes. The purpose of this research is to find out about derivational and inflectional morphemes, affixation processes, and the most dominant types of affixes found in the novel. This study uses mixed methods with an exploratory sequential design. The data sources used in this research are primary source and secondary source. In collecting data, researchers used observations and documentation. In analyzing data, the researcher uses content analysis, which included the process of unitizing, sampling, coding, data reduction, abductive inferring, narrating, and calculating. The result of the research focuses showed there are 265 words divided into 83 derivations and 182 inflections. The derivational morpheme is classified into 8 processes. While the inflectional morpheme is classified into 8 processes. While the most dominant type of affix derivation is verb to noun with total frequency of 37 words or 44, 57%. Then, the most dominant type of affix inflection was plural in 91 words or 50%.